Induced ncRNAs Allosterically Modify RNA Binding Proteins in cis to Inhibit Transcription - Wang, Xiangting (2008)
With the recent recognition of non-coding RNAs (ncRNAs) flanking many genes1-5, a central issue is to fully understand their potential roles in regulated gene transcription programs, possibly through different mechanisms6-12. Here, we report that an RNA-binding protein, TLS, serves as a key transcriptional regulatory sensor of DNA damage signals that, based on its allosteric modulation by RNA, specifically binds to and inhibits CBP/p300 HAT activities on a repressed gene target, cyclin D1 (CCND1). Recruitment of TLS to the CCND1 promoter to cause gene-specific repression is directed by single stranded, low copy number ncRNA transcripts tethered to the 5′ regulatory regions of CCND1 that are induced in response to DNA damage signals. Our data suggest that signal-induced ncRNAs localized to regulatory regions of transcription units can act cooperatively as selective ligands, recruiting and modulating the activities of distinct classes of RNA binding co-regulators in response to specific signals, providing an unexpected ncRNA/RNA-binding protein-based strategy to integrate transcriptional programs.